Seropositivity for MIA and S100 in patients with gastrointestinal carcinomas - Wagner, Volker; Rudi, Jochen; Näher, Helmut; Stremmel, Wolfgang (Medical oncology, 2000)
Serum levels of melanoma inhibiting activity (MIA) and S100, both markers in malignant melanoma, are increased only in few patients with non-melanocytic tumors. We examined a series of serum samples from patients with colorectal (CRC) (N=56), gastric (GC) (N=43), pancreatic (PC) (N=29), hepatocellular (HCC) (N=30), cholangiocellular and gallbladder carcinoma (CCC) (N=18). MIA and S100 were measured by commercially available assays. Positive serum levels for MIA and S100 were found in 16.1% and 5.4% of the patients with CRC, 11.6% and 9.3% with GC, 34.5% and 13.8% with PC,0% and 30% with HCC and 16.7% with CCC, respectively. All patients with sera positive for either MIA or S100 suffered from advanced tumors and received palliative treatment. Elevated serum levels of MIA and S100 are frequentin patients with gastrointestinal cancer. Further investigation is warranted to define the role of MIA or S100 seropositivity in gastrointestinal cancer with regard to follow-up.